GE_GERICHTE P/10945/2023 vom 18. Oktober 2023 - GE Cour de justice (2023)
ORDONNANCE DE CLASSEMENT;SOUPÇON;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DISJONCTION DE CAUSES | CPP.319; CP.123; CP.126; CP.177; CP.144; CPP.29; CPP.30